Consumer protection and online dispute resolution in Malaysia: online shopping / Aini Afidah Mashudi, Siti Rohani Ali and Siti Nabilah Baharim - Mashudi, Aini Afidah; Ali, Siti Rohani; Baharim, Siti Nabilah (2008)
Our study is concerning on consumer protection in Malaysia specifically on online shopping. Even though online shopping had grown rapidly around the globe, which offers more benefits and more practical than traditional shopping but still, many people never intend to practice it on several reasons. When we click the mouse, browsing and make selection online shopping starts. Online shopping offers high level of convenience but still the security of consumers is questionable. Many cases regarding misuse of consumer personal information and encroachment of privacy had hinder consumers from trying this type of online transaction. We will discuss issues regarding on formation of electronic contract (e-contract) because it is relevant so as regardless traditional shopping or online, contractual issues would still arise. We will look into problems that arisen because of unreliable and unsecured online transaction. Data protection and privacy would be the main issues that we will discuss. Furthermore, the act that had been enacted also sometimes does not provide enough protection for consumers in online transaction. As our study will focus on online shopping in Malaysia, we will look into Consumer Protection Act 1999, E-Commerce Act 2006 and other relevant statutes pertaining issues on consumer protection in cyber world. In addition, we will discuss too on the relevancy of using online dispute resolution as a redress for consumers in online transaction. Even though it is in its infancy in Malaysia, but some efforts should be made in order to ensure its effectiveness and to prove that it is the best way to resolve disputes in online transaction.